Multifarious methods in the pursuit of quality: More "ands" and fewer "ors". Issue 1 (22nd October 2022) - van Zanten, Marta
Abstract : The author highlights accreditation's role in increasing public availability of information and its use (or lack thereof) to evaluate institutions for the purpose of gatekeeping IMGs.